Analisis Faktor Faktor yang Mempengaruhi Behavioural Intention - Wibowo, Agung Edy (UP2M SEKOLAH TINGGI ILMU EKONOMI GALILEO, 2017)
This research aimed to analyze the influenced factors towards behavioural intention. Sample size was 400 respondent, taken with purposive sampling method, through survey. In this research, analyzing technique will be conducted by using multiple linear regression analysis. The result of this research find out several points, namely; for first hypothesis; e-service quality has significantly impact toward behavioural intention,, accepted. Itâs proven by the significance level of motivation at 0.000. And for the result of secondary hypothesis; consumer satisfaction has significantly impact toward behavioural intention, accepted. Itâs proven by the significance level of consumer satisfaction at 0.000. Meantime for third hypothesis; attitude toward the website has significantly impact toward behavioural intention, accepted, Â because it had significance level at 0.048.